2008
DOI: 10.4103/0301-4738.42425
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular tissue migration of silicone oil after silicone oil tamponade: A histopathological study of enucleated silicone oil-filled eyes

Abstract: Retrospective clinical and histopathological review of eight silicone oil-filled enucleated eyeballs using light microscopy was carried out in our department of ocular pathology during a period of six years. In all cases, silicone oil vacuoles, both free and incorporated within macrophages were seen in all the retinal layers. Silicone oil vacuoles were seen in the optic nerve, choroid, retinal pigment epithelium, corneal stroma, iris and ciliary body stroma, preretinal and subretinal membranes and retro-cornea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 3 publications
0
22
0
1
Order By: Relevance
“…The mechanism of how SO endotamponade causes retinal thinning remains unclear. Previous studies have shown the migration of SO into the ocular tissues, including the optic nerve, and the subsequent induction of an inflammatory response mediated by macrophages in several human and animal studies [12][13][14][15][29][30][31][32] ; however, retinal thinning occurs not only in severe cases but also in mildto-moderate cases; thus, it is difficult to conclude that SO intraretinal infiltration is the only cause for the retinal thinning. There have also been reports on the changes in visual outcome and retinal thickness caused by treatment with SO endotamponade.…”
Section: Discussionmentioning
confidence: 86%
“…The mechanism of how SO endotamponade causes retinal thinning remains unclear. Previous studies have shown the migration of SO into the ocular tissues, including the optic nerve, and the subsequent induction of an inflammatory response mediated by macrophages in several human and animal studies [12][13][14][15][29][30][31][32] ; however, retinal thinning occurs not only in severe cases but also in mildto-moderate cases; thus, it is difficult to conclude that SO intraretinal infiltration is the only cause for the retinal thinning. There have also been reports on the changes in visual outcome and retinal thickness caused by treatment with SO endotamponade.…”
Section: Discussionmentioning
confidence: 86%
“…Because there is essentially no normal anatomical communication between the globe and the intracranial subarachnoid space, they hypothesized a route of entry based on pathological findings of migration of silicone vesicles into the optic nerve parenchyma in enucleated globes after silicone tamponade. 3,6 They speculated that the silicone might have entered the optic nerve through the atrophic optic disc as a result of increased intraocular pressure, then coalesced, and eventually migrated into the perioptic subarachnoid space. Communication between the perioptic and subarachnoid spaces would allow silicone to enter the ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…But long-term silicone oil tamponade could evoke a series of complications, and the emulsification of silicone oil is a grave one. Some researchers reported that VSO were found on retinal surface, intraretina and in optic nerve after silicone oil was removed from patients [14][15][16][17]. The hRPE cells we obtained were from normal individuals, and they could indicate normal behavior.…”
Section: Discussionmentioning
confidence: 89%